Theoretical Aspects of the Use of Electronic Educational Resources in Professional Activity of Future Teachers of Technology - Smyrnova , Iryna (Journal of Vasyl Stefanyk Precarpathian National University, 2017)
In this paper, we tried to determine the requirements for ESM, to study theoretical aspects of electronic educational resources in the professional activity of future teachers. The results created by the introduction of our course “Methodology development and use of electronic educational resources” for future teachers of technology ITOS in the process of professional specialty “Technology” in the educational process of higher educational institutions of Ukraine. The article states the rapid development of computer hardware and computer software, IT technologies have an opportunity to significantly develop the field of electronic educational resources. This is due to the emergence of global networks where information technologies have become the second paradigm, which is based on the current understanding of electronic educational resources. We determined that the dynamism inherent in information technology, enabling expectations of new approaches that will change the meaning of electronic educational resources